A PHENOMENOLOGICAL STUDY OF STUDENTS’ EXPERIENCES USING GOOGLE DOCS FOR COLLABORATIVE ONLINE VIRTUAL TEAM WRITING INSTRUCTION - Chalermsup Karanjakwut; Arnantawut Tiang-uan (MOJES: Malaysian Online Journal of Educational Sciences, 2024)
Online collaborative learning for developing English writing skills has been widely recognised for decades as a key approach to enhancing students’ learning achievement and experiences through technology. However, it is generally one-way learning. Therefore, the virtual team concept has recently been applied to online learning and teaching to raise the level of two-way interaction between a teacher and students. This research explored the experiences of a group of second-year English majors collaborating online as a virtual team during writing instruction. Google Docs was the synchronous online platform deployed in this study. Data from six participants in semi-structured interviews were studied qualitatively using a phenomenological analysis method. The findings revealed the students’ perceptions of opportunities in the online environment, the collaborative learning environment, knowledge construction, preference for group activities, collaborative activities, teacher feedback, and accessibility (including pressure and communication). Difficulties with grouping, monopolisation, time arrangement, free-rider effects, familiarisation and communication, emerged from the interviews. Factors related to social interaction, usability, prior experience with computer-mediated communication, technology, and support for learners were found in this study. We conclude with the disagreement of the students’ voices regarding their experience and learning with the Google Docs application, suggesting the need for further development.